Dipolar magnetism in assembled Co nanoparticles on graphene. Issue 31 (30th July 2018) - Chan, Yao-Jui; Huang, Chih-Heng; Chang, Yin-Ming; Lu, Yi-Ying; Wu, Shih-Yu; Wei, Der-Hsin; Kuo, Chien-Cheng
Abstract : The magnetic properties of the assembled Co nanoparticles on graphene were studied using X-ray magnetic circular dichroism (XMCD), magneto-optical Kerr effects, and a modeling simulation. Abstract : The magnetic properties of the assembled Co nanoparticles on graphene were studied using X-ray magnetic circular dichroism (XMCD), magneto-optical Kerr effects, and a modeling simulation. We demonstrate that the superparamagnetic nanoparticles reveal a ferromagnetic phase when they are assembled on graphene. The moderate increase of the XMCD asymmetry and magnetization with coverage for this assembly indicates a dipolar-mediated magnetism, which is further verified by a model simulation considering the dipolar interaction between neighboring nanoparticles. Furthermore, C K-edge spectra reveal visible dichroism at the π* state of graphene, which indicates the existence of a spin-polarized interface state, while the assembled Co nanoparticles reveal a ferromagnetic phase. These results suggest an efficient route to stabilize the ferromagnetic phase of nanostructures on graphene by tailoring dipolar interactions, which is essential to realize a higher efficiency of spin injection in graphene-based spintronics.